(untitled) (REMUNOM, 2024)
The continuous evolution of AI and intelligent machines in agriculture is emphasized by their positive impact on the sector’s growth. Precision agriculture, for example, integrates technology into farming practices to reduce labor costs, precisely apply inputs, optimize agricultural performance, and enhance environmental sustainability by avoiding issues such as water scarcity. The transition to AI-based methods in agriculture can be complex and slow due to the integration of modern technology with existing systems, lack of adequate training, and challenges in choosing the right tools for effective communication. Implementing AI in agriculture requires significant training and education for operators and farmers to handle advanced technologies practically. Considering that the evolution of precision agriculture involves the increased application of fully autonomous and intelligent machines in farming, better weather forecasting, and advanced information analysis for better decision-making. Investments in agricultural research have led to the development of advanced technologies such as autonomous machines, robots, and software that surpass human capabilities in agricultural tasks. Agriculture 4.0 introduces high levels of technology into farming activities, capable of integrating tasks such as planting, irrigation, pest and disease control, harvesting, storage, and transportation, with AI playing a crucial role in current and future farming practices. Autonomous machines equipped with AI, such as tractors and harvesters, offer precise operations, 24-hour functionality, waste reduction, increased productivity, and economic cost management in agricultural activities.